2020
DOI: 10.1177/0363546520951202
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Subspinous Impingement in Borderline Hip Dysplasia and Outcomes Compared With a Matched Cohort With Nondysplastic Femoroacetabular Impingement

Abstract: Background: Arthroscopic management of femoroacetabular impingement (FAI) in the setting of borderline hip dysplasia is controversial. Recently, there has been increased awareness of a prominent anterior inferior iliac spine (AIIS) resulting in subspinous impingement. Purpose/Hypothesis: The purpose was to report outcomes of arthroscopic subspinous decompression in patients with symptomatic hip impingement and borderline hip dysplasia compared with a matched cohort with nondysplastic FAI. Addressing a prominen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Many authors have noted excellent short- to midterm results after hip arthroscopy in these patients. 1,2,4-10,16-18,26,34 Patient selection is important, as multiple risk factors for poorer outcomes have been cited. These include increasing age, 13,14,17 hip osteoarthritis, 13,22,29 ligamentum teres tears, 23 untreated FAI, 5 labral debridement, 15 a smaller vertical-center-anterior angle, 13 and cartilage injury.…”
mentioning
confidence: 99%
“…Many authors have noted excellent short- to midterm results after hip arthroscopy in these patients. 1,2,4-10,16-18,26,34 Patient selection is important, as multiple risk factors for poorer outcomes have been cited. These include increasing age, 13,14,17 hip osteoarthritis, 13,22,29 ligamentum teres tears, 23 untreated FAI, 5 labral debridement, 15 a smaller vertical-center-anterior angle, 13 and cartilage injury.…”
mentioning
confidence: 99%
“…The results of the present study in athletes echo those of previous studies in the general population. Feghhi et al 17 evaluated outcomes of arthroscopic subspine decompression in patients with symptomatic hip impingement and borderline dysplasia as compared with a matched cohort with nondysplastic FAIS. In their study, patients with borderline dysplasia and SSI demonstrated significantly more intra-articular damage and underwent more microfracture, capsular plication, and ligamentum teres debridement than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that compared AIIS impingement with borderline hip dysplasia and nondysplastic FAIS revealed that arthroscopic AIIS decompression is a safe and effective treatment. 10 A clinical issue is the decision regarding the area of decompression within the AIIS lesion. In this regard, an important cadaveric study was conducted by Hapa et al 14 They showed that the direct head of the rectus tendon has a broad insertion on the AIIS; however, the area devoid of tendon provides a “safe zone” for subspine decompression in cases of symptomatic AIIS impingement.…”
Section: Discussionmentioning
confidence: 99%